Understanding Associations Between Exposure to Violent Pornography and Teen Dating Violence Among Female Sexual Minority High School Students - Herbitter, Cara (Journal of interpersonal violence, 2022)
Previous research indicates that teen dating violence (TDV) is more common among sexual minority than heterosexual adolescents, with approximately half of female sexual minority adolescents (SMA) endorsing TDV victimization in the last year. In samples of adolescents without regard to sexual orientation, exposure to violent pornography is associated with TDV, but this relationship has not been assessed in female SMA. The current study sample consisted of 10th-grade high school students aged 14?17 who identified as cisgender females (N = 1,276). Data were collected from a baseline survey prior to the delivery of a sexual assault prevention intervention. Female SMA had 2.54 times the odds (95%CI [1.75, 3.69]) of being exposed to violent pornography and 2.53 times the odds (95%CI [1.72, 3.70)]) of TDV exposure compared to heterosexual girls. Exposure to violent pornography was not associated with involvement in TDV among female SMA, controlling for episodic heavy drinking (aOR = 2.25, 95%CI [0.88,6.22]).Given the relatively higher rates of violent pornography and TDV exposure among female SMA compared to heterosexual girls, it is critical that sex education curricula address these experiences and meet the needs of adolescents of all sexual orientations. Future research can assess how these TDV interventions might be tailored for female SMA. Although we did not find that exposure to violent pornography was associated with TDV among female SMA, these investigations should be replicated with larger data sets, given that the association between exposure to violent pornography and engagement in TDV was in the expected direction.